Dire l’indicibile, a quantum exhibition - AAVV (Il Colle di Galileo, 2024)
The second Quantum revolution is expected to influence society as a whole thanks to the groundbreaking technologies it introduces. As part of its effort in the dissemination of Quantum Physics and Quantum Technologies, in November 2023, the National Institute of Optics (CNR-INO) in Florence organised ”Dire l’indicibile: l’entanglement quantistico” an exhibition open to the general public with the aim of spreading knowledge of quantum Physics and quantum technologies. The goal of the exhibition was to boost awareness of these developing technologies in local communities, using interactive exhibits designed for the occasion, while also investigating the impact this event had on its visitors.